Report on professional attachment with Golden Village Multiplex Pte Ltd. - Poh, Yvonne Yin Sian. (2009)
The following report will present firsty the background and purpose of the attachment programme, followed by a brief introduction of the company. It will also highlist some of the promotions undertaken during the eight weeks. These promotions evolve around the film "12 Storeys" and "Paradise Road" and cover various aspects such as publicity, press related areas, event organization and management, joint promotion exercises and the production of collaterals. The report also attempts to show that the above is helpful in putting into perspective what had been taught in theory. In addition, it can been seen from the report that through the process of going about these tasks, a clearer picture of marketing in practice is presented.